2021
DOI: 10.3233/jad-201271
|View full text |Cite
|
Sign up to set email alerts
|

Resting State Alpha Electroencephalographic Rhythms Are Differently Related to Aging in Cognitively Unimpaired Seniors and Patients with Alzheimer’s Disease and Amnesic Mild Cognitive Impairment

Abstract: Background: In relaxed adults, staying in quiet wakefulness at eyes closed is related to the so-called resting state electroencephalographic (rsEEG) rhythms, showing the highest amplitude in posterior areas at alpha frequencies (8–13 Hz). Objective: Here we tested the hypothesis that age may affect rsEEG alpha (8–12 Hz) rhythms recorded in normal elderly (Nold) seniors and patients with mild cognitive impairment due to Alzheimer’s disease (ADMCI). Methods: Clinical and rsEEG datasets in 63 ADMCI and 60 Nold in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Specifically, groups of ADD and ADMCI patients were characterized over the Nold control seniors by the decrease in alpha power density or estimated cortical source activities and decreased theta-delta power density or estimated cortical source activities. [6][7][8][9][10][11][12] At the individual level, previous rsEEG studies reported that the ratio of rsEEG power density at delta, theta, and alpha frequency bands was able to classify ADMCI patients at the individual level with an accuracy of around 80% (AUROC). Other research consortia obtained similar results with rsEEG recordings in standard hospital settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, groups of ADD and ADMCI patients were characterized over the Nold control seniors by the decrease in alpha power density or estimated cortical source activities and decreased theta-delta power density or estimated cortical source activities. [6][7][8][9][10][11][12] At the individual level, previous rsEEG studies reported that the ratio of rsEEG power density at delta, theta, and alpha frequency bands was able to classify ADMCI patients at the individual level with an accuracy of around 80% (AUROC). Other research consortia obtained similar results with rsEEG recordings in standard hospital settings.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the individual alpha 1 and alpha 2 bands were computed as follows: alpha 1 from TF to the frequency midpoint of the TF-IAF range and alpha 2 from that midpoint to IAF. The other bands were defined based on the standard fixed frequency ranges used in the reference study 11 : beta 1 from 14 to 20 Hz, beta 2 from 20 to 30 Hz, and gamma from 30 to 40 Hz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This EEG wave is the most common wave seen during awake states ( Adrian and Matthews, 1934 ). Global alpha power is more abnormal in younger MCI and AD patients ( Babiloni et al, 2021b ). Posterior alpha sources are more abnormal in male MCI/AD patients ( Babiloni et al, 2021c ).…”
Section: Electroencephalography Event-related Potential Neurofeedback...mentioning
confidence: 99%